Alienation Occurred in “Melancholia” Movie - Irene Rosalina (Nuris Journal of Education and Islamic Studies, 2022)
A movie may mirror a person's experiences in life and is not just for amusement. Movies include moral lessons that viewers may learn from. It educates us about attitudes, behaviors, language, culture, and culture. It's simple for individuals to appreciate movies visually as literary. Melancholy is appropriately examined utilizing the alienation idea based on the movie's plot. Human alienation was at first a social phenomenon in contemporary life (Darma, 1995 in Efendi, 2005). Social psychology refers to this as alienation. According to Melville's 1996 short story "About Bartleby," alienation is a type of self-separation from everyone and everything, including other people (Bloom, 2009). The alienated emotion toward anything, including internal and exterior components, is the complexity of estrangement in and of itself. This could incite someone to be antagonistic toward other individuals or society. The purpose of this study was to identify the ways in which Justine, the main character in the film Melancholia, was alienated. The article utilizes some of the earlier research on melancholia that has been conducted by a small number of academics in order to analyze the film. This research was produced under the auspices of the alienation theory. This research fell under the heading of literature philosophy. The Lars von Trier film Melancholia, which was released in 2011, served as the study's main source of information. Analyzing the presence of alienation in the film involved observing, transcribing the screenplay, and categorizing the conversation in accordance with the subject of alienation. A type of mental disease in humans called alienation is defined by emotions of being foreign or weird to others, to nature, the environment, God, and even to oneself. Alienation is discussed in connections with oneself, other people, society, objects/nature, and capitalism in Lars von Trier's film Melancholia. The social lives of those who don't take care about their families' or children's issues are criticized in this movie. They don't express any emotional existence; only physical existence